The complete protections induced by the oil emulsion vaccines of the novel variant infectious bursal disease viruses against the homologous challenges indicating the important roles of both VP2 and VP1 in the antigenicity and pathogenicity of the virus - Wang, Weiwei; Huang, Yu; Zhang, Yan; Qiao, Yuanzheng; Shi, Jun; Huang, Jianni; Huang, Teng; Wei, Tianchao; Mo, Meilan; He, Xiumiao; Wei, Ping (Frontiers in Veterinary Science, 2024)
Novel variant infectious bursal disease virus (nvIBDV) is an emerging genotype (A2dB1b) that can cause severe and prolonged immunosuppression in young chickens.Despite current commercial vaccines being proven to lack complete protection against nvIBDV, it remains unclear whether the oil emulsion inactivated vaccines (OEVs) of the homologous and heterologous virus or booster immunization can provide effective protection. In this study, OEVs with two types of nvIBDV isolates QZ191002 (A-nv/Bnv) and YL160304 (A-nv/B-HLJ0504 like) were prepared and evaluated the protective effects of OEVs plus the booster immunizations with different current commercial vaccines against the challenge of nvIBDVs. Results from vaccination-challenge experiments showed that nvIBDV could break through the protection provided by only one immunization dose of the commercial vaccines, with the protection rates ranging from 40%-60%. Interestingly, even booster immunization with different commercial vaccines, the protection rates could only be increased to 60%-80%. As expected, only the OEVs of the homologous virus could provide 100% protection against the homologous nvIBDV, which could induce high-level specific antibodies, ameliorate target organ damage, and significantly reduce the viral load of the bursal in the challenged chickens. Notably, YL160304-OEV performed better than QZ191002-OEV, providing 100% protection not only against the challenge of homologous strain, but also against that of heterologous QZ191002 strain. Antibody levels of the immunized chickens gradually increased after a short decline, and reached the highest level on the age of 28 days. Similarly, the percentages of lymphocytes CD4+, CD8+ T and B in peripheral blood lymphocytes (PBLs) were significantly increased on 21d and 28d.Notably, despite the nvIBDV OEVs initially induced a delayed responses in the early stages but ultimately reach higher levels of CD4+ and CD8+ T lymphocytes. The results of study suggest that even booster immunization with different commercial vaccines cannot provide complete protection against nvIBDV, while the OEVs made by the nvIBDVs can provide full protection. Moreover, YL160304-OEV exhibits a broader protective spectrum against different nvIBDV strains, making it a potential candidate for the development of new vaccine.